2014
DOI: 10.1186/1743-0003-11-144
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer measurement of upper extremity movement after stroke: a systematic review of clinical studies

Abstract: The aim of this review was to identify and summarise publications, which have reported clinical applications of upper limb accelerometry for stroke within free-living environments and make recommendations for future studies. Data was searched from MEDLINE®, Scopus, IEEExplore and Compendex databases. The final search was 31st October 2013. Any study was included which reported clinical assessments in parallel with accelerometry in a free-living hospital or home setting. Study quality is reflected by participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 24 publications
0
85
0
Order By: Relevance
“…Accelerometers have been shown to be useful in monitoring gait (eg, overall physical activity level, step activity and gait alterations) in boys with DMD and in children with other neurological diseases . Most of the experience with the use of accelerometers in the UEs is in adult patients with stroke and multiple sclerosis . Uswatte et al showed that if complementary self‐reported measures are used simultaneously they can provide rich information about UE activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerometers have been shown to be useful in monitoring gait (eg, overall physical activity level, step activity and gait alterations) in boys with DMD and in children with other neurological diseases . Most of the experience with the use of accelerometers in the UEs is in adult patients with stroke and multiple sclerosis . Uswatte et al showed that if complementary self‐reported measures are used simultaneously they can provide rich information about UE activities.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies with accelerometers to measure UE function, various parameters were used. Intensity (or movement counts) of movement was recommended as a parameter in several studies . Koene et al questioned the relationship between measured intensity and UE function in children with mitochondrial disease because a high level of nonpurposeful activity influences the registration of the parameter intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The inertial sensors such as accelerometer, gyroscope, or combination of both termed as inertial measurement unit (IMU), can capture kinematic information about the body movement when placed over appropriate body parts [8,9,10]. Some studies reported successful applications of the accelerometers in monitoring the daily living ability of stoke survivors [11,12,13]. However, in these studies, participants needed to wear accelerometers for a long time like 24 h or even 3 days during the active/inactive periods.…”
Section: Introductionmentioning
confidence: 99%
“…Related work shows that inertial sensors can provide information on the amount of arm movement and time spent using the arm in daily life [24]. Quality of movement and range of motion (ROM) are typically generated through robotic technologies or opto-electronic systems [18].…”
Section: Methodsmentioning
confidence: 99%